2017
DOI: 10.1038/ng.3947
|View full text |Cite
|
Sign up to set email alerts
|

A functional genomics predictive network model identifies regulators of inflammatory bowel disease

Abstract: A major challenge in inflammatory bowel disease (IBD) is the integration of diverse IBD data sets to construct predictive models of IBD. We present a predictive model of the immune component of IBD that informs causal relationships among loci previously linked to IBD through genome-wide association studies (GWAS) using functional and regulatory annotations that relate to the cells, tissues, and pathophysiology of IBD. Our model consists of individual networks constructed using molecular data generated from int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
199
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(234 citation statements)
references
References 78 publications
9
199
0
2
Order By: Relevance
“…The discovery of NOD2 as the first, and most important, susceptibility gene1 2 was then followed by identification of over 200 other loci,3 4 but these genetic contributions together likely only explain 19%–26% of the hereditary variance of IBD 5. Genetic studies have identified defects in innate immunity in Crohn disease (CD) and altered barrier function in Ulcerative Colitis (UC) as some of the key players in disease susceptibility 6 7…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of NOD2 as the first, and most important, susceptibility gene1 2 was then followed by identification of over 200 other loci,3 4 but these genetic contributions together likely only explain 19%–26% of the hereditary variance of IBD 5. Genetic studies have identified defects in innate immunity in Crohn disease (CD) and altered barrier function in Ulcerative Colitis (UC) as some of the key players in disease susceptibility 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Detailed descriptions of these data sets are available in the published studies. 11,18,19 2.3 | Transcriptome-wide association study The FUSION software was applied to the GWAS summary data of IBD for tissue-related TWAS analysis. Briefly, FUSION computed the gene expression weights of various tissues using a small set of individuals with both genotype and gene expression data.…”
Section: Mrna Expression Profiles Of Ibdmentioning
confidence: 99%
“…Recently, Peters et al used individual networks constructed from molecular data generated from intestinal samples isolated from three populations of patients with IBD at different stages of disease, including two adult and pediatric cohorts of IBD. As a result, they developed a predictive model of the immune component of IBD that informs causal relationships among loci previously linked to IBD through GWAS using functional and regulatory annotations that relate to the cells, tissues, and pathophysiology of IBD.…”
Section: Beyond Genetics: Ibdomics—systems Biology and Integrative Mementioning
confidence: 99%
“…This network revealed potential key drivers of IBD pathogenesis. Among the key drivers were numerous known VEO‐IBD genes, but also inborn errors of immunity and new candidates that were showed to have a role in inflammatory immune response …”
Section: Beyond Genetics: Ibdomics—systems Biology and Integrative Mementioning
confidence: 99%